205k views
5 votes
How to simplify (4b)^3 in only positive exponents ?

1 Answer

8 votes

Answer:

We conclude that:


\left(4b\right)^3=64b^3

Explanation:

Given

Let the expression


\left(4b\right)^3

To determine

Simplify the expression in only positive exponents

Simplifying the expression

Given the expression


\left(4b\right)^3

Apply exponent rule:
\left(a\cdot \:b\right)^n=a^nb^n


\left(4b\right)^3=4^3b^3

as 4³ = 64, so


=64b^3

Therefore, we conclude that:


\left(4b\right)^3=64b^3

User Mitesh Dobareeya
by
5.5k points